One-hour postload plasma glucose levels as a new criterion for assessing insulin secretion in obese children - O. V. Vasyukova; P. L. Okorokov; V. A. Peterkova (Сахарный диабет)
BACKGROUND: Incidence of Type 2 Diabetes Mellitus (T2DM) and associated dysglycemic conditions, increasing the risk of diabetes development, continues to rise worldwide, most notably due to ever-growing obesity rate. Early identification of the persons who are exposed to the risk of T2DM development holds much significance for prevention of both this disease and associated cardiometabolic complications.AIM: To study characteristics of insulin secretion and insulin sensitivity among obese children and adolescents versus the glycemic level 60 minutes (GL60) after the standard oral glucose tolerance test (OGTT).METHODS: This open-label comparative cross-sectional study involved 613 children in the age between 6 and 17.9 years old with constitutive-exogenous obesity, divided into 2 groups: 173 patients with GL60 level ≥ 8.6 mmol/L and 440 children with GL60 level < 8.6 mmol/L. They underwent a screening for dyslipidemia, non-alcoholic fatty liver disease, arterial hypertension and impaired glucose tolerance (IGT). Insulin secretion was evaluated on the basis of maximal (IRI max), average level (IRI avg) of insulin in the course of OGTT and insulinogenic index (IGI), insulin resistance (IG) — by Matsuda index.RESULTS: The groups were comparable in the terms of age, sex, sexual maturation stage and obesity level. Children with GL60 level ≥ 8.6 mmol/L were characterized by higher IR (Matsuda 2.8 ± 2.3 vs 3.5 ± 2.2, р < 0.01), hyperinsulinemia (IRI max 190.0 ± 59.5 vs 157.1 ± 63.4 μU/ml, р < 0.001, IRI avg 115.3 ± 59.7 vs 90.2 ± 54.1 μU/ml, p < 0.001) along with low IGI value (1.84 ± 1.62 vs 2.61 ± 1.3, р < 0.01), which is indicative of the first phase insulin secretion impairment. The lowest IGI values were found among the "GL60 level ≥ 8.6 mmol/L" group patients with IGT (1.4 ± 0.9). Besides, the patients with GL60 level ≥ 8.6 mmol/L are characterized by the higher rate of metabolic complications in the form of impaired glucose tolerance, arterial hypertension, fatty hepatosis and steatohepatitis.CONCLUSIONS: GL60 level ≥ 8.6 mmol/L can be used as an additional marker for metabolically complicated obesity among children and adolescents with a high risk of the carbohydrate metabolism disorder development.